A tale of two bellies: systematics of the oval frogs (Anura: Microhylidae: Elachistocleis Parker, 1927) - Novaes-E-Fagundes, Gabriel; Lyra, Mariana L. [UNESP]; Loredam, Vinicius S. A. [UNESP]; Carvalho, Thiago R. [UNESP]; Haddad, Celio F. B. [UNESP]; Rodrigues, Miguel T.; Baldo, Diego; Barrasso, Diego A.; Loebmann, Daniel; Avila, Robson W.; Brusquetti, Francisco; Prudente, Ana L. C.; et al. (Oxford Univ Press, 2022)
Oval frogs (Elachistocleis) have a broad geographic distribution covering nearly all of South America and parts of Central America. They also have a large inter- and intraspecific variation of the few morphological characters commonly used as diagnostic traits among species of the genus. Based on molecular data, we provide the most complete phylogeny of Elachistocleis to date, and explore its genetic diversity using distance-based and tree-based methods for putative species delimitation. Our results show that at least two of the most relevant traditional characters used in the taxonomy of this group (belly pattern and dorsal median white line) carry less phylogenetic information than previously thought. Based on our results, we propose some synonymizations and some candidate new species. This study is a first major step in disentangling the current systematics of Elachistocleis. Yet, a comprehensive review of morphological data is needed before any new species descriptions can be properly made.
Keywords: Herpetology; Morphology; Narrow-mouthed frogs; Neotropics; Phylogeny; Synonymy; Taxonomy